Estimating the population size of transgender women in San Francisco using multiple methods, 2013. Issue 1 (2nd January 2018) - Wesson, Paul; Qabazard, Redha F.; Wilson, Erin C.; McFarland, Willi; Raymond, H. Fisher
ABSTRACT: Purpose : To estimate the number of adult transgender women (TGW) in San Francisco and to provide an example of how estimation can be conducted. Methods : Using nine different services accessed by the TGW population, the service multiplier, integrated into a respondent-driven sampling (RDS) survey of TGW, was used to calculate nine estimates of the TGW population in San Francisco. Both the successive sampling method, also integrated into the RDS survey of TGW, and a population proportion from the literature each calculated an additional estimate of the TGW population. The median of all 11 estimates was calculated to present a single estimate of the TGW population in San Francisco. Results : The median of estimates was 978 TGW in San Francisco (plausibility bounds 635 – 1, 400). This estimate is consistent with known cases of HIV among TGW and surveys on the prevalence of infection in the TGW population. Conclusion : Using multiple methods, we estimate the TGW population size to be 0.13% of the San Francisco population. Despite small numbers, TGW bear a disproportionate burden of HIV infection in San Francisco. TGW are a priority for HIV care and prevention services.